Fabrication and electrochemical performance of pseudocapacitive ABO2-type AgFeO2@C - Singh A.N.; Yadav A.K.; Gupta A.; Rath C.; Singh P. (My University, 2025)
To make effective utilization of renewable energy sources, a highly efficient large-scale energy storage solution is needed that can fill the gap between the batteries (high energy density) and the capacitors (high power density). Supercapacitors are being a bridge between batteries and capacitors, suffer from low energy density, and need to be further upgradation for utilization as a grid-level energy storage solution. A higher energy density can be achieved by constructing an asymmetric cell (ASC) in which both, the electrodes (positive and negative) are worked in a separate potential window. Pseudocapacitive ABO2-type electrode in the form of an asymmetric cell (ASC), AgFeO2@C//K0.4MnO2. xH2O is envisaged here as high high-performing battery-type supercapacitor cell to develop large-scale energy storage solutions. Herein, crystallites of K0.4MnO2. xH2O were successfully grown via a facile chemical flux method that gives a birnessite-type layered structure having a lateral dimension in the range of 2–5 μm. Thus, the incorporation of birnessite- K0.4MnO2. xH2O as a positive electrode (cathode), and the thin carbon layer coated AgFeO2 as a negative electrode (anode) in aqueous 1 M Na2SO4 electrolyte in the form of ASC exhibited high energy density as well as power density with excellent cycle life up to cell voltages close to 1.8 V. The presented battery-type supercapacitor cell can deliver a maximum energy density equivalent to 61.51 Wh kg−1 and a power density of 450 W kg−1 at a current density of 0.5 A g−1, which is substantially larger than the previously reported aqueous electrolyte-based asymmetric supercapacitor devices. The newly developed high-voltage aqueous asymmetric battery-type supercapacitors device has a low-cost and enviro-friendly, that can replace currently market-available hazardous lead-acid batteries for fast energy storage applications. © 2023
K0.4MnO2. xH2O battery-type supercapacitive asymmetric cell for large-scale energy storage applications